Is the Youth Aware of E-scooter Use Regulations? Evidence from the Region of Sicily - Tiziana Campisi; Socrates Basbas; Andreas Nikiforiadis; Thomas Papas; Giovanni Tesoriere (Transactions on Transport Sciences)
Micromobility became a trend over the last few years in many European cities, but also worldwide. This trend emerged after the appearance of many e-scooter sharing services, which mainly operated in a dockless way, i.e. without fixed stations. Shared e-scooters were initially recognized as an ideal transport mode for first/last-mile trips, that could be perfectly combined with other modes and mainly public transport. However, the excessive use of shared e-scooters created also several issues in the cities. These issues are mainly associated with traffic safety and public space invasion. The main cause for these issues was that the cities were not adequately prepared for the appearance of this new transportation mode, and no appropriate regulations were established. Yet, this need has already led to the establishment of regulations in many European cities, including Italian ones. Despite the existence of regulations, it is still unclear if the users follow the rules, but also if the users are aware of the rules. In order to shed some light in this issue, a questionnaire survey was carried out in the region of Sicily. The survey focused on the youth, i.e. people aged between 18 and 26 years old. The selection of the specific age group was made because users of this age could be more vulnerable and disobedient, but also because the youth is the one that was mainly attracted by e-scooters based on previous studies. Finally, 302 responses were collected. Initial results show that some of the regulations are well known between the youth; yet, there are other regulations that are not clear yet. The results lay the foundation for forming appropriate campaigns for raising awareness among students and young adults regarding the micromobility regulations and the appropriate use of e-scooters in general. Such campaigns are considered essential for efficiently integrating micromobility in recent transportation systems.